Avaliação da funcionalidade pulmonar de trabalhadores expostos a produtos químicos em oficinas automotivas - Chaves, Thiago José Vieira (2016)
Automotive workshops’ workers are included in the exposed populations to occupational hazards as an important set of diseases, injuries and deaths of workers comes from the desktop. The use of aromatic hydrocarbons such as benzene, which is used for automotive paint, with the improper use of safety equipment may result in health risks. In this context, the objective of this work is evaluate the pulmonary functionality of exposed workers to Benzene and Benzene’s derivatives during automotive paint in automotive workshops on Teresina – Piauí. One way to monitor and follow is using the spirometry exam, the best exam to evaluate the pulmonary functionality. Moreover, ventilation and exhaustion systems in the automotive workshops and persistent trainings for the correct identification and utilization of the safety equipament, with the monitoring program of the quality in the desktop. This work was performed with 80 workers, of which 40 workers were destined to the control group of workers not exposed to chemical substances and 40 workers were destined to the test group of workers exposed to chemical substances, distributed in 7 automotive workshops. This present work evidence that was not observed statically significant difference between control group and test group in automotive workshops on Teresina – Piauí. All the automotive workshops had ventilation and exhaustion systems, but the most of the workers said that they don’t know about the corrects use and save the safety equipments. However, was observed a positive correlation (Fisher Test) with respiratory problems, who worked 5 years or more in automotive workshops and smoking (10 cigarettes/day) for 10 years. We can conclude the necessity to elaborate a monitoring program of the automotive workshops and be alert about the workers’ health.